Penilaian Manfaat Ekowisata Hutan Mangrove Desa Budo Kecamatan Wori Kabupaten Minahasa Utara - Awali, Kifli Riyaldy; Saroinsong, Fabiola B.; Kalitouw, Devitha Windy (AGRI-SOSIOEKONOMI, 2023)
This research aims to analyze the benefits of mangrove ecotourism using the approach of visitors and the community around the mangrove forest ecotourism in Budo Village. This research was conducted in February-April 2022. The method used in this study is a quantitative descriptive method. Data regarding the benefits of mangrove forest ecotourism were carried out using direct interview techniques to 40 respondents from mangrove forest ecotourism visitors and 13 communities around mangrove forest ecotourism who were in guard VI. The data obtained were analyzed using a descriptive method which was tabulated in the form of a table. Based on the results of ecotourism research, mangrove forests are used by visitors as tourist attractions. 65% of respondents considered that access / ease of reach to the location of mangrove forest ecotourism in Budo Village was very easy to reach, 78% of respondents considered that mangrove debt ecotourism in Budo Village had a very beautiful view, 49% of respondents assessed that ecotourism in the mangrove forest of Budo Village had a variety of objects/ the number of spots varies greatly, 47% of respondents rated the ecotourism of the mangrove forest of Budo Village as very clean, 63% of respondents rated the service and safety of ecotourism of the mangrove forest of Budo village as very satisfactory, 48% of respondents rated the service of eating places for ecotourism of the mangrove forest of Budo village as very satisfactory, and 78 %. Budo Village mangrove forest ecotourism provides many benefits for the community around Budo Village mangrove forest ecotourism, both direct and indirect benefits. The direct benefits for the people of Budo Village can be used as a place for entrepreneurship in the form of MSMEs, home stays, parking lots, and cafes that can increase the income of the community around the Budo Village mangrove forest, the physical indirect benefits of mangrove forests are useful as a barrier to coastal abrasion, intrusion barriers ( infiltration) seawater, and windbreaks.